PENERAPAN LABORATORIUM VIRTUAL DALAM MENINGKATKAN PEMAHAMAN KONSEP IPA MAHASISWA PGMI - Arda Arda (Koordinat Jurnal MIPA, 2022)
This research is an experimental research (quasi experimental design). It aims to determine the application of virtual laboratory to improve understanding of science concepts. Subjects of this research were PGMI students class of 2020. The results of data analysis using the t-test showed that students understanding of science concepts who received learning using a virtual laboratory differed significantly from students who received conventional learning. The gain based on the results of data analysis using the gain normalization of the experimental class was 0.60 and the control class was 0.41. It means that there is improvement on the students of PGMI science concept in medium category. The increase in understanding of science concepts in the experimental class was higher than in the control class.